Analysis of methodological problems in research on the genetics of behavior in Ukraine - Філіпцова, О. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The analysis of the problems associated with the peculiarities of the formation and work with a population sample in research in the field of human behavior genetics in Ukraine was done. In the absence of the material promotion psychogenealogical information collection efficiency is 23% of all individuals involved during the trial. Collection efficiency of psychometric material is 15–84 % of the total content of the tests used. Higher collection efficiency of the material was observed in females (67%) compared to males (33%). Collection efficiency for the genetic analysis in the related pairs was quantitatively organized in a following way: "mother–daughter" > "mother–son"> "father–daughter" > "father–son".